Catalogues of Some Useful Classes of Circular Designs in Blocks of Three Different Sizes to Control Neighbor Effects - Akbar Fardos; Abdul Salam; Jamshaid Ul Hassan; Hurria Ali; Khadija Noreen; Rashid Ahmed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Minimal neighbor designs minimize the bias raised due to the neighbor effects using the minimum number of experimental units. Minimal circular balanced and strongly balanced neighbour designs can be constructed only for odd v (number of treatments to be compared). For v even, minimal Quasi Rees and nearly strongly balanced neighbor designs are constructed. In this article, the construction procedures of these four classes are described. Catalogues of these designs in blocks of three different sizes are also presented which provide the readymade solution to the experimenters and researchers.